Behavioral changes following alterations in the composition of a captive bachelor group of western lowland gorillas (Gorilla gorilla gorilla). Issue 6 (29th October 2018) - Gartland, Kylen; McDonald, Monica; Braccini Slade, Stephanie; White, Frances; Sanz, Crickette
Abstract : Western lowland gorillas ( Gorilla gorilla gorilla ) in zoos are housed in family or bachelor groups to maximize social opportunities. While wild bachelor groups are transient, all‐male groups in zoos may be maintained for many years. Captive bachelor groups need to be carefully monitored, particularly during periods of demographic transition, due to the possibility for escalating aggression. We examined behavioral changes in a bachelor group at the Saint Louis Zoo following two significant alterations in group composition: (1) the introduction of two immature related males in 2011 and (2) the death of the dominant silverback in 2015. Behavioral data were collected on group members using 15 min focal observations with 30‐s instantaneous scans, totaling 185.25 hr for the first transition and 115.25 hr for the second transition (with equal effort in baseline and transition periods). We found that the addition of the two subadult males resulted in a significant increase in affiliation in the group often initiated by these new younger individuals, while the rate of abnormal and aggressive behavior did not change significantly. The rate of abnormal, aggressive, or affiliative behavior in the group also did not change significantly following the death of the dominant silverback. Overall, we conclude that this bachelor group and potentially others can endure possibly destabilizing social transitions and remain cohesive social units. Behavioral changes will result from transitions, but the effect on individuals or impact on the group will vary. Therefore, longitudinal monitoring of bachelor groups will be essential for effective management during any major changes.